Public enterprises and private purposes - Chaudhuri Sudip
A basic premise underlying much of the critical writing on public enterprise is that there is something wrong with public enterprises per se. The auther contests this view that public enterprises are inherently inefficient and contends that a crucial aspect has been the objectives and the priorities with which the public enterprises have been run. The focus of the paper is on the manufacturing enterprises under the central government
Keywords: Government Business Enterprises -- India